Surgical selection and regional lymph node dissection for stage I second primary lung cancer patients following surgery for stage I first primary lung cancer - Wu, Xiao; Jiang, Youhua; Chen, Qixun; Wang, Jiangfeng; Li, Jianqiang (Frontiers in Oncology, 2023)
Studies investigating surgery for the second primary non-small cell lung cancer (SPNSCLC) patients are rare. The aim of this study was to explore the effects of surgical methods and regional lymph node (LN) dissection on lung cancer-specific mortality (LCSM) for stage I SPNSCLC patients following the surgery of stage I first primary non-small cell lung cancer (FPNSCLC). Data on patients diagnosed with stage I SPNSCLC after the surgery of stage I FPNSCLC were extracted from the Surveillance, Epidemiology, and End Results (SEER) database. Cumulative incidence function (CIF) curves, competing risk model and propensity score matching (PSM) were adopted to compare the LCSM among different subgroups (including surgery and regional LN dissection). A total of 238 stage I SPNSCLC patients were extracted from the SEER database. Overall, the 5-year LCSM rate was 29.8% (CI: 23.1%-36.5%) for the whole cohort. Both before and after PSM, lobectomy had a similar LCSM incidence with sublobectomy, and ≥4 regional LN dissection had a significantly lower LCSM incidence than 1~3 regional LN dissection. In addition, patients undergoing 1~3 regional LN dissection had a comparable incidence of LCSM to those without LN dissection. Stage I SPNSCLC patients tended to gain more survival benefits when surgeons dissect ≥4 regional LN. Allowing for the comparable LCSM incidence of sublobectomy to lobectomy, sublobectomy may be a reasonable choice for thoracic surgeons when performing surgery for these patients.